Characteristics of 10 patients with paraneoplastic rheumatologic musculoskeletal manifestations. Issue 3 (May 2014) - Yamashita, Hiroyuki; Ueda, Yo; Ozaki, Takashi; Tsuchiya, Haruka; Takahashi, Yuko; Kaneko, Hiroshi; Kano, Toshikazu; Mimori, Akio
Abstract Objectives. To evaluate the possible correlation of malignant neoplasms and paraneoplastic rheumatologic syndromes. Methods. We studied a series of 10 patients with paraneoplastic rheumatological syndromes collected from our Division of Rheumatic Disease between 2006 and 2012. Results. Our series consisted of four males and six females, with a mean age of 65.5 years (range, 57–78 years). Of the 10 patients recruited, six had hematological malignancies and four had solid cancers. Malignancies were diagnosed after rheumatic symptoms were reported in all patients. Compared to solid tumors, hemopathy was diagnosed at a later time point (16.2 vs. 7.3 months). Extra-articular symptoms were associated with rheumatologic musculoskeletal manifestations in 100% of the patients. Polyarthritis was the main rheumatologic musculoskeletal manifestation (50% of the patients). The other manifestations were oligopolyarthritis and polymyalgia rheumatic-like symptoms (20% of the patients). Symmetric arthritis was present in 60% of the patients, and the remaining patients developed asymmetric arthritis. Musculoskeletal manifestations completely regressed in 66.7% of the patients after cancer therapy. When tumor relapse was observed, rheumatic symptoms did not recur in any of our patients (100%). Conclusions. Rheumatic disorders with atypical clinical presentation in older patients, poor response to usual treatment and systemic features such as weight loss and clinical findings compatible with well-recognized paraneoplastic syndromes should alert clinicians to the possible coexistence of an occult malignancy. Especially in cases of paraneoplastic rheumatic/musculoskeletal manifestations associated with hemopathy, the primary disease is unlikely to have manifested yet, making the diagnosis difficult. Thus, caution is required.